2017
DOI: 10.1534/g3.117.043737
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq of Rice Yellow Stem BorerScirpophaga incertulasReveals Molecular Insights During Four Larval Developmental Stages

Abstract: The yellow stem borer (YSB), Scirpophaga incertulas, is a prominent pest in rice cultivation causing serious yield losses. The larval stage is an important stage in YSB, responsible for maximum infestation. However, limited knowledge exists on the biology and mechanisms underlying the growth and differentiation of YSB. To understand and identify the genes involved in YSB development and infestation, so as to design pest control strategies, we performed de novo transcriptome analysis at the first, third, fifth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 103 publications
(109 reference statements)
2
13
0
Order By: Relevance
“…We provide the first phylogeny comprising all subfamilies of Crambidae and including pyraloid molecular data sets from major previous phylogenetic studies (Heikkilä et al., 2015; Kawahara & Breinholt, 2014; Léger et al., 2019; Mally et al., 2019; Mutanen et al., 2010; Regier et al., 2012), from published genomes or transcriptomes (Challis et al., 2016; Renuka et al, 2017) and our own sequences. Our data set provides placement for Cathariinae, Cybalomiinae and Linostinae, although without well‐supported sister relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provide the first phylogeny comprising all subfamilies of Crambidae and including pyraloid molecular data sets from major previous phylogenetic studies (Heikkilä et al., 2015; Kawahara & Breinholt, 2014; Léger et al., 2019; Mally et al., 2019; Mutanen et al., 2010; Regier et al., 2012), from published genomes or transcriptomes (Challis et al., 2016; Renuka et al, 2017) and our own sequences. Our data set provides placement for Cathariinae, Cybalomiinae and Linostinae, although without well‐supported sister relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A representative subset of the taxa from phylogenetic studies of Léger et al (2019) and Mally et al (2019) were also included. Sequences of interest were retrieved from published transcriptomes of Cnaphalocrocis medinalis (Guenée, 1854), Myelobia smerintha (Hübner, 1821) (Kawahara & Breinholt, 2014) and Scirpophaga incertulas (Walker, 1863) (Renuka et al, 2017), and from the whole genomes of Amyelois transitella (Walker, 1863) and Chilo suppressalis (Walker, 1863) on the LepBase interface (Challis et al, 2016;ensembl.lepbase.org). Taxon sampling is summarized in Table S1.…”
Section: Taxon Samplingmentioning
confidence: 99%
“…The identified CSPs were named after the CSPs from Bombyx mori [22]. To compare the CSPs expressed in C.auricilius with that in other closely related insect species, the phylogenetic analysis was performed by using previously reported CSPs in C. suppressalis [25], B.mori [22] , Scirpophaga incertulas [26] , Sesamia inferens [27] . Phylogenetic analysis showed that all the 92 CSPs from the five insect species revealed well-supported clades displaying clear orthologous relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Adults of YSB were collected from one plot of ICAR-IIRR, Hyderabad farm, and females were selected based on the morphological features and were subjected to whole-genome sequencing [ 13 , 14 ]. The DNA was isolated from the female adult YSB using a standard CTAB method and checked for quality and quantity on 0.8% agarose gel and Nanodrop, respectively.…”
Section: Methodsmentioning
confidence: 99%